Word formation study in the context of historic stylistics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the formation process of historic stylistics. The study problems of word formation stylistic potentials are formulated. The semantic and pragmatic necessity of differentiation Ukrainian word formation resources is substantiated. The reasonability and outlook of study stylistic aspect of word formation are motivated.
Keywords: derivative semantics; historic stylistics; word formation potentials; stylistic word formation; stylistic functions